Trade-offs between sight lines and escape habitat determine spatial strategies of risk management by a keystone herbivore - Douglas W. Morris; Sundararaj Vijayan (Canadian Science Publishing, 2018)
Prey individuals possess four basic strategies to manage predation risk while foraging: time allocation, space use, apprehension, and foraging tenacity. But there are no direct tests of theory detailing how spatial strategies change and covary from fine to coarse scales of environmental variability. We address this shortcoming with experiments that estimated space use and vigilance of snowshoe hares while we measured foraging tenacity in artificial resource patches placed in risky open versus safe alder habitat. Hares employed only two of eight a priori options to manage risk. Hares increased vigilance and reduced foraging in open areas as the distance from cover increased. Hares did not differentiate between open and alder habitats, increase vigilance at the coarse-grained scale, or reduce vigilance and foraging tenacity under supplemental cover. Hares were more vigilant in the putatively safe alder than in the purportedly risky open habitat. These apparently paradoxical results appear to reflect a trade-off between the benefit of alder as escape habitat and the cost of obscured sight lines that reduce predator detection. The trade-off also appears to equalize safety between habitats at small scales and suggests that common-sense predictions detailing how prey reduce risk may make no sense at all.